Phytochemical Screening, Total Flavonoids and Antioxidants of Kalanchoe Pinnata Linn. Leaves - Qomaliyah, Eka Nurul; Indriani, Nurul; Rohma, Atika; Islamiyati, Ricka (Current Biochemistry, 2023)
Kalanchoe pinnata Linn. or in Indonesia known as cocor bebek, this plants grow well in temperate and tropical regions. Cocor bebek is used to treat several diseases including skin diseases, wound healing, kidney stones, gallstones, diabetes. The pharmacological activities of cocor bebek leaves have been reported as anti-inflammatory, anti-oxidant and anti-microbial. The objective of this study is to determine the metabolite content of cocor bebek leaves, total flavonoid levels and antioxidant activity. Observations of secondary metabolites of cocor bebek leaves were carried out through qualitative secondary metabolite screening, while total flavonoid levels were carried out quantitatively UV-VIS with quercetin as a comparison, atioksidan activity through DPPH molecular inhibition testing. The results of this study indicate that cocor bebek leaves contain alkaloids, flavonoids, saponins, triterpenoids, tannins and phenols. 200gr of cocor bebek leaves obtained % yield extract is 14.63%. The total favonoid content obtained was 8.77% of quercetin, while the antioxidant inhibition of DPPH molecules obtained IC50 of 97.42 ppm.